Design Concept : Integrating and Creating ‘Third Place’ in Schools’ Environment - Raja Nur Syaheeza, Raja Mohd Yazit; Elina, Mohd Husini; Atta Idrawani, Zaini (Human Resource Management Academic Research Society, 2020)
Interactions between younger and older generations that leads to social connectivity is important. Introductions of boarding schools segregated students wi th the surrounding society. The segregation causes total institution that negatively impacted the students’ social behavior, thus causes the students to be socially detached with the community. Adapting Third Place urban theory in smaller scopes such as educational institution can create school layout design that emphasizes social interactions. It can be defined as public spaces that serves as a rejuvenation or escapism tool from First Place (home) and Second Place (workplace). In boarding schools, First Place is the dormitories and Second Place is the classrooms. This paper focuses on the conceptual idea of integrating Third Place with boarding school design. Observation in an educational hub in Pengkalan Chepa, Kota Bharu shows the street hawkers’ stalls allow a common area for teachers, students, government servants and the local community to interact between each other. Surrounding the site are other institution such as schools, residentials, a prison and a mosque. By merging the Third Place of the community with the boarding school, opportunity for the students to socially interact increases in theory. This paper introduces a new conceptual idea for school layout design.